Defining the community of interest as thematic and cognitive regions. (November 2017) - Phillips, Daniel W.; Montello, Daniel R.
Abstract: When deciding where to draw the boundaries for electoral districts, officials often strive to ensure that communities of interest are not split up but kept wholly within those boundaries. But what constitutes a community of interest is vague, with legal and academic sources describing either a thematic region with shared demographic and land-use traits, or a cognitive region that is meaningful to people and commonly agreed upon. This study, conducted in the city of Santa Barbara, California, seeks to identify communities of interest at the sub-city level as both thematic regions—by clustering Census tracts and land parcels according to classes of relevant variables—and cognitive regions—by surveying residents about the size and locational extent of their community and finding areas of agreement. We then assess the degree to which the two types of regions overlap as a way to evaluate how well the two meanings correspond. We also examine the amount of overlap between the two sets of regions and the city council electoral districts that were recently created in Santa Barbara. Our study finds that the two types of regions correspond relatively well to each other in this test city, but that the electoral districts correspond more to the thematic regions, understandable given that the district creation made no attempt to survey residents about their beliefs.